PENGARUH VACA, VAHU DAN STVA TERHADAP NILAI PERUSAHAAN PADA PERUSAHAAN PERBANKAN YANG TERDAPAT DI BEI - Siska Aprianti (JURNAL RISET TERAPAN AKUNTANSI, 2018)
This study aims to examine the effect of intellectual capital variable consisting of variables VACA, VAHU and STVA to company value. Population used in this research is banking company that listed in BEI year 2011-2014. Based on the sample selection criteria that have been determined then the sample used in this study are as many as 22 banking companies listed Indonesia Stock Exchange with the period of annual financial reports from 2011-2014. Data analysis method used in this research using the help of computer program that is program SPSS Versi 20.0. The result of research indicate that partially, intellectual capital variable which consist of VACA have influence to company value, while variable of VAHU and STVA have no influence to company value. While the simultaneous test results indicate that the variable of intellectual capital consisting of VACA, VAHU and STVA have a significant effect on firm value.